IMPACT OF PB, NI AND CD ON THE GERMINATION OF BARLEY SEEDS, VARIETY JADRAN - Vasić, Predrag; Jakšić, Tatjana; Đelić, Gorica (Bulletin of Natural Sciences Research, 2020)
The aim of this study was to determine the effect of lead, nickel and cadmium on the germination of barley seeds (Hordeum vulgare L.) of Jadran variety. Based on the percentage of germination, germination energy, and root and hypocotyl length, authors done an analysis of the effects of PbCl2, NiCl2, CdCl2 solutions, in concentrations of 103 mol/m3, 102 mol/m3, 10 mol/m3, 1 mol/m3, 10 -1 mol/m3, 10-2 mol/m3. The results showed that germination and germgrowthin stress conditions which are caused by heavy metals depend on the type of metal and its concentrations. The most toxic effect of alltested solutions had CdCl2, and the weakest toxic effect had PbCl2.
Keywords: Hordeum vulgare L.; Lead; Nickel; Cadmium; Germination